Analysis of Duolingo Application Usability Based on the System Usability Scale (SUS) - Khaerun Nizam; Asta Gilang Duha; Bayu Wibisana; M. Hasan Amir Husen (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2026)
Duolingo is one of the most widely used interactive language learning applications globally, integrating text, audio, visuals, animations, and gamification elements. Although numerous studies have examined its effectiveness in improving language skills, usability evaluations using standardized instruments such as the System Usability Scale (SUS) among Indonesian college students remain scarce. This research gap motivates the present study, which evaluates the user experience of Duolingo through a descriptive quantitative approach. The novelty of this study lies in providing localized usability evidence within the Indonesian higher education context, specifically targeting active college students. A purposive sampling technique was applied, involving 31 active students from semesters 1 to 8 who have used or are currently using Duolingo. Data were collected via a 10-item SUS questionnaire distributed through Google Form and WhatsApp and analyzed using the standard SUS calculation formula developed by Brooke (1996). The average SUS score obtained was 63.95, categorized as OK. The distribution of ratings shows 51.6% OK, 12.9% Excellent, 12.9% Good, and 22.6% Poor. These results indicate that while Duolingo is generally acceptable, improvements are still needed in interface consistency and onboarding experience for new users. The findings imply that Duolingo developers should prioritize interface redesign for Indonesian users, and educators should consider usability factors when selecting digital learning tools. This study contributes empirical evidence for future research on user experience evaluation in interactive multimedia-based learning applications.